Association of Thyroid-Stimulating Hormone Levels with Microvascular Complications in Type 2 Diabetes Patients - Qi, Qi (Med Sci Monit, 2017)
BACKGROUND: Subclinical hypothyroidism (SCH) is typically featured by elevated serum concentration of thyroid-stimulating hormone (TSH). This study aimed to determine the relationship between TSH levels and microvascular complications in type 2 diabetes patients. MATERIAL/METHODS: A total of 860 type 2 diabetes patients were enrolled in this cross-sectional study. Subjects were evaluated for anthropometric measurements, thyroid function, diabetic retinopathy, and diabetic kidney disease. TSH was divided into 3 levels: 0.27–2.49 mU/l, 2.5–4.2 mU/l, and >4.2 mU/l. RESULTS: Among the participants, 76 subjects (8.8%) were diagnosed with subclinical hypothyroidism (SCH) (male: 6.6% and female: 11.8%). The prevalence of diabetic retinopathy did not differ among the groups (P=0.259). Of the 860 type 2 diabetic subjects, we further excluded invalid or missing data. Therefore, 800 and 860 subjects were included in our study of diabetic retinopathy (DR) and diabetic kidney disease (DKD), respectively. The frequencies of microalbuminuria and macroalbuminuria differed significantly among the different groups. The frequency of DKD was significantly different among the 3 groups (P=0.001) and was higher in subjects with higher TSH levels. After an adjustment for confounding variables, TSH levels were significantly associated with DKD (P<0.001). When compared with subjects with TSH 0.27–2.49 mU/l, the frequency of DKD was higher in subjects with TSH >4.20 mU/l (OR 1.531, 95% CI 1.174–1.997) and with TSH 2.50–4.20 mU/l (OR 1.579, 95% CI 1.098–2.270). However, TSH levels was not significantly correlated with DR (P=0.126). CONCLUSIONS: Type 2 diabetic patients with higher TSH values had a higher prevalence of DKD.